Analysis of the impact of financial literacy on students' financial management behavior - Abdul Rasyid (Journal of Economics and Business (JECOMBI), 2023)
Financial skills and understanding, or better known as financial literacy, must be possessed by everyone starting from an early age. Good financial literacy makes it easier for someone to manage their finances. The purpose of this research is to determine the description of financial literacy and financial management behavior among students, as well as to determine the influence of financial literacy on student financial management. This research uses quantitative methods with descriptive research type. The population of this study were students who understood financial inclusion in Jayapura City while the sample taken was 30 people. The research results show that from the t test, the t count is 8.433 > t table 1.985, so it can be concluded that the Financial Literacy variable (X) influences the financial management behavior variables of students in Jayapura City. The magnitude of the influence of financial literacy on students' financial management behavior is 41.8%, while the remaining 58.2% is explained by other variables not discussed or included in this research.